جهود الشيخ الخليلي الدعوية في مواجهة التيار الشيوعي بزنجبار: The Preaching Efforts of Sheikh Al-Khalili in Confronting the Communist Movement in Zanzibar - Al Toqi, Khalid Ahmed Saleh; Yusof, Muhammed; Salem Qatawneh, Mohammad Abdelhamid (Al-Basirah Journal, 2024)
Sheikh Ahmed bin Hamad Al-Khalili stands as one of the most prominent scholars who actively opposed the ideology of atheism, dismantling its foundations. From his early years, he devoted himself to exposing its fallacies, notably its recurring claim that religions contribute to the destruction of civilization and the eradication of humanity. In contrast, Sheikh Al-Khalili maintained an entirely different perspective, shaped by his direct encounters with the atheist-communist movement in Zanzibar. This study thus aims to clarify the atheistic perspective on humanity by examining Sheikh Al-Khalili’s preaching efforts against the atheist-communist movement in Zanzibar. The study employed historical, descriptive, and analytical methodologies, concluding that atheist communism perpetrated brutal massacres in Zanzibar, decimating 4% of the local population. Communism entered Zanzibar during a period of neglect in Islamic preaching and a decline in religious education, which fueled African resentment toward Arabs. Despite his youth and the general lack of awareness among his contemporaries regarding the true nature of communist ideology, Sheikh Al-Khalili recognized the principles and dangers of atheistic communism early on. His efforts included advocating for the establishment of religious institutes in rural areas, raising youth awareness about the communist movement, and devising plans to rescue the deteriorating educational landscape in the country.